Die Sprachfrage in der Bildung der Kindergartenpädagogen (Training and Practice : Journal of Educational Sciences, 2015)
The European nurseries were established in the 19th century. The example set in England was soon followed by Hungary, when in 1828 countess Terese of Brunsvik sacrificed her own fortune and founded a nursery in Buda.The ’nursery case’ became an instrument of spreading national language throughout the multi-ethnic Hungarian Kingdom. It is true, the first nursery pedagogues were men with German mother tongue, and the first nurseries were established in places where German speaking citizens were in majority. Nevertheless, an association supporting nurseries of the Reform era, aimed to propagate the Hungarian language.At the same time, sources prove that both educators and children spoke many languages in the nurseries of the 19th century. However, there is no evidence in any sources, that multilingualism would have blocked the spiritual development of children. I believe this could be an appropriate reason for experts, who oppose language education in nurseries.